Remote sensing of a high-Arctic, local dust event over Lake Hazen (Ellesmere Island, Nunavut, Canada). (1st February 2021) - Ranjbar, Keyvan; O'Neill, Norm T.; Ivanescu, Liviu; King, James; Hayes, Patrick L.
Abstract: A dust plume rising to a maximum altitude of about 1 km above the springtime high-Arctic terrain of Lake Hazen, Nunavut, Canada was detected using a diverse array of passive and active, satellite-based remote sensing techniques. We were able to broadly characterize the 532 nm optical depth and particle size of the upper plume (0.5 ± 0.2 and 15–25 μm radius limits respectively). To our knowledge this is the first satellite-based remotely sensed, overland capture of what is an ubiquitous aeolian process across the Arctic: drainage winds inducing dust plumes that are funneled along basin pathways to spread over the water and land surfaces at the outlets of those pathways. The identification and characterization of the Lake Hazen plume was challenging given that there is little development of passive and active remote sensing techniques over Arctic terrains. Our findings suggest that Arctic-adapted remote sensing techniques that incorporate a priori information on dust optical properties can be exploited to identify and characterize locally generated plumes. Highlights: A springtime, high-Arctic dust plume over Lake Hazen, Nunavut, Canada was detected using satellitebased remote sensing. This is likely the first remotely sensed overland capture of a local dust plume over the Arctic. Arctic-adapted RS techniques incorporating dust optical properties can be exploited to investigatelocally generated plumes.